Diversity of Gluten Proteins in Landrace Wheat Varieties Grown in Different Ecological Regions of Uzbekistan (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Here was described full polymorphism of electrophoretic spectra of gliadines in wheat landraces of Uzbekistan comparing with commercial and newly zoned cultivars. It was conducted work on 21 landraces, 2 new and one commercial commercial variety that it was revealed 40 variation in electrophoretic spectra.